Anatomical and Histological study of the Tongue of wild adult male Rabbits (Oryctolagus cuniculus f. domestica) in AL-Najaf province - Aqeel Mohsin Mahdi AL-Mahmodi (Kufa Journal for Veterinary Medical Sciences, 2016)
Macro and Microscopical explorations of the tongue in the ten of the adult male Rabbits collected from AL-Najaf city markets, this work expect will provide a support for future research and subsequent clinical applications as regards the biology of the tongue. After rabbits preparation the tongue distinguished then the shape, position, dimensions were record. The apex of the tongue was almost rounded. The body was square-shape thickening decreased gradually toward root. Root which slopes ventrocaudally toward the base of the epiglottis. Torus linguae at the caudal part of the dorsal surface. Lateral surface of tongue contain several fossa touching the premolar teeth. The mean length of the total tongue, apex, body, and root were (4.5 ± 0.5 cm), (1.25 ± 0.23 cm), (2.95 ± 0.2 cm), and (0.9 ± 0.26 cm) respectively. The mean width of the apex, body, and root at the widest part were (1 ± 0.49 cm), (1 ± 0.17 cm), and (1.26 ± 0.22 cm) respectively. Skeletal muscle fibers and loose connective tissue surrounded by stratified squamous epithelium keratinized at the dorsal and lateral lingual surfaces, non-keratinized at the ventral lingual surface. Filiform papillae heavy distribution on the dorsal surface of body, scanty at the apex, at the lateral surface of the body they are smaller than body papillae and longer than apex papillae. Circumvallate papillae were oval-shape, surrounded by a moat-like furrow, taste buds on the dorsal and lateral sides. Foliate papillae were leaf-like non-keratinized; with taste buds on the lateral walls. Fungiform papillae hade broad rounded keratinized surface, with taste buds on the dorsal surface. Lamina propria -submucosa was loose connective tissue with rich bundles of collagen fibers.